Efeitos da combinação de agrotóxicos e do patógeno Nosema ceranae no desenvolvimento de Apis mellifera africanizada - Tadei, Rafaela (2020)
Bee populations have declined in several parts of the world, possibly due to a combination of biotic and abiotic factors, such as pesticides, pathogens and forest fragmentation. Since the larval stage, bees are exposed to combination of pesticides by food and contact that can harm their health and capacity to combating pathogens, such as the microsporidium Nosema ceranae. The present study aimed to assess whether exposure to the combination of pesticides in the early stage of bee development changes the rates of infection and effects caused by the pathogen N. ceranae. For this, Apis mellifera larvae from three healthy colonies were transferred to in vitro conditions and received an artificial diet containing 2% of pesticides from the third to the sixth day of feeding. The larval bioassay was composed of six experimental groups: I - Control, II - Solvent control, III - Clothianidin insecticide, IV - Pyraclostrobin fungicide, V - Combination: insecticide + fungicide, VI - Commercial pyraclostrobin fungicide - Comet®. The total consumption of clothianidin and pyraclostrobin was 0.17 ng / larva and 0.69 ng / larva, respectively. These individuals were kept at 34ºC and humidity controlled until the emergency. One day after the emergency, half of the individuals in each experimental group were orally inoculated with 100,000 N. ceranae spores. Six days after inoculation, the midgut of the bees was submitted to dissection, fixation and microtomy for histological, histochemical and immunofluorescence evaluation. From the histological sections, quantitative analyzes of the infection rate, morphometric of the epithelial thickness and semi-quantitative analyzes of cellular changes in the midgut were performed. Deleterious effects on post-embryonic development were not observed in the experimental groups. Larval exposure to pesticides made subsequent adults more susceptible to the actions of the pathogen Nosema ceranae, increasing epithelial lesions in the midgut. Among the experimental groups, the insecticide showed the highest cytotoxicity to the midgut and increased the rates of cellular infection to the inoculated spores. No synergism was observed in individuals exposed to a combination of pesticides, but co-exposure favored infection with the pathogen. The commercial formulation of the fungicide did not enhance the effects of the active principle on the ventricular epithelium of adult bees. Thus, this study is the first to assess larval exposure to combinations of pesticides followed by inoculation with N. ceranae and showed that larval exposure to sublethal doses of these pesticides can affect the health of subsequent adult individuals.